Turning around coast-based schools: An interpretive narrative analysis of a report on school reform in English coastal communities. (November 2021) - Parfitt, Anne
An interpretive narrative inquiry approach is adopted to shed light on the improvement agendas applied in a specific set of coastal schools. The unifying thread between the focal cases is that they had been designated as failures and made notorious through association with their communities' tainted reputations. These schools feature in a report published by the Future Leaders Trust, which is used as the resource for this paper. The taken for granted deficit discourses implicit in the accounts of how these schools were reformed are relied upon by the school leaders and other stakeholders to justify why they needed to be turned around. These assumptions that come to the fore through analysis, demonstrate that the socioeconomic contexts found in the jaded English coastal communities are not engaged with. Importing approaches that draw on communities' resistance to relegation could, potentially, build positive discourses that lead to communities reclaiming educational opportunities in such schools, one clear example being that of Countesthorpe in Leicestershire, UK, in the 1970s.